Prealbumin level at biochemical marker of nutritional assessment in premature infants - Achmad Surjono Achmad Surjono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
Controversies in adequate nutrition for premature infants still exist. No single anthropometric or biochemical measures currently available are reliable for premature nutritional assessment.The aim of this study is to determine the usefulness of serial prealbumin serum levels in identifying adequacy of nutritional intake in premature infants during their neonatal period. A group of 18 infants ranging in birthweight between 1030-2050 g, nursed in the Dr. Sardjito Hospital until one month of age were included for study. Breast and formula milk were given in increasing amount and depending upon acceptance 120 Cal/kg of body weight/day should be achieved. Peripheral capillary blood samples were obtained for prealbumin examinations (by radial-immunodiffusion method) on the first day and at weekly interval afterwards. The infants were weighed daily and serum albumin was examined on 14 and 28 days of age.It turns out that the mean serum prealbumin in the first day of life was 7.9 Â± L8 mg% and a significant increment levels on weekly measurements were obtained. It is shown that no correlation was found.between the prealbumin and albumin levels. Body weights correlated poorly with serial prealbumin values.It seems that prealbumin, with a short half-life of 1.9 days can be used as a sensitive nutritional assessment in premature infants. Modifying of adequate protein and caloric provision could be applied early to prevent malnutrition in the neonatal period of premature infants.Key Words: prealbumin - serum albumin - premature infants - nutritional assessment - caloric requirement